(untitled) (Research, Society and Development, 2020)
Phytonematodes cause considerable losses in agricultural production worldwide, their main form of control is through the use of chemical nematicides. However, this form of control is inefficient due to the high costs and negative impacts on human health and the environment, requiring new control alternatives. The use of organic fertilizers can modify and provide improvements in the quality of the soil promoting the growth of plants and can also reduce the incidence of phytomatomatoids. The objective of the study was to evaluate the potential of three organic fertilizers, applied in solid or liquid form, in the control of Pratylenchus brachyurus in soybeans. The experiment was carried out in a 3x2+1 factorial scheme, with three replications. Two organic compounds and a vermicompost were applied to the soil in solid or liquid form and the control received only mineral fertilizer. For this, soybean plants were grown in a greenhouse, with the addition of 2,000 specimens of P. brachyurus to the soil. The soybean produced greater dry mass of the aerial part when the three organic fertilizers were added to the soil in solid form in relation to the treatment with mineral fertilization. Among the forms of application, the solid provided better performance in the parameters of the plant superior to the liquid. The solid vermicompost increases the dry mass of the aerial part of the plant grown in soil infested with P. brachyurus.